Play brigade project Brincadas as insurgent pedagogy: play, agency, and transformation in the context of BRICS+ education - Liberali, F.C.; Lemos, M.; Modesto-Sarra, L.K. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only This article presents the Brincadas-COLINA project, a Brazilian educational initiative that emerges at the intersection of geopolitical changes and epistemic reconfigurations in BRICS+ societies. Based on the principles of engaged multiliteracy, curriculum de-encapsulation, and Insurgent Pedagogy[1], the project brings together children, educators, and families from quilombola, indigenous, and urban periphery communities in collective learning experiences. In this article, we focus on the first Brincadas session in 2023. Data were analyzed through videos, photos, interviews, artistic productions, and collaborative reflections. Data analysis was carried out through critical reflection actions: describe, inform, confront, and reconstruct (Smyth, 1989). The results demonstrate how artistic, dialogical, and embodied activities allowed participants to resignify ethical-political suffering and exercise collective agency. By situating Brincadas within broader pedagogical movements in the Global South, this study contributes to theorizing education as a tool and outcome for social and epistemic justice. [1] Translator's note: Insurgent Pedagogy is a term describing an educational approach that opposes traditional, authoritarian, or oppressive teaching methods. It focuses on developing critical thinking, resisting social and political injustices, and actively engaging students in the process of knowledge creation and social transformation. Эта статья рассказывает о проекте Brincadas-COLINA - бразильской образовательной инициативе, которая возникла в условиях изменений мировой политики и новых подходов к обучению в странах BRICS+. Brincadas-COLINA основан на принципах активного обучения через мультимедийные средства, переосмысления учебных программ, а также на идеях мятежной педагогики[1]. В проекте участвуют дети, учителя и семьи из общин киломболо, коренных и городских бедных районов, которые вместе учатся и делятся опытом. В статье описывается первая сессия этого проекта в 2023 году. Для анализа использовались видео, фотографии, интервью, художественные работы и совместные размышления участников. Анализ проводился в четыре шага: описание ситуации, предоставление информации, обсуждение проблем и поиск решений (по методике Smyth). Результаты показывают, что художественные и диалоговые активности помогли участникам переосмыслить свою боль, вызванную несправедливостью, и обрести силу для совместных действий. Исследование показывает, как такие подходы и проекты могут способствовать развитию образования как инструмента и результата социальной и эпистемической справедливости. [1] Мятежная педагогика (Insurgent Pedagogy) - это термин, описывающий образовательный подход, который противостоит традиционным, авторитарным или подавляющим методам обучения. Он ориентирован на развитие критического мышления, сопротивление социальной и политической несправедливости, а также на активное вовлечение учащихся в процесс создания знаний и осуществление социальных преобразований (прим. переводчика).